Maternal mortality, safe abortion, and the anaesthetist. (December 2022) - Wong, Cynthia A.; Galley, Helen F.; Leslie, Kate
Summary: Reproductive health is an active area of practice and research for anaesthetists, intensivists, and pain medicine specialists. The purpose of the British Journal of Anaesthesia is to promote the health, welfare, and safety of all persons by disseminating knowledge to further our understanding of anaesthetic principles and improve practice and skills. This includes supporting safe abortion care as an integral part of safe reproductive health.